Discrimination of 15 Amazonian Anopheline Mosquito Species by Polymerase Chain Reaction—Restriction Fragment Length Polymorphism. Issue 3 (9th February 2022) - Vezenegho, S B; Issaly, J; Carinci, R; Gaborit, P; Girod, R; Dusfour, Isabelle; Briolant, S
Abstract: Precise identification of anopheline species is paramount for incrimination of malaria vectors and implementation of a sustainable control program. Anopheline mosquitoes are routinely identified morphologically, a technique that is time-consuming, needs high level of expertise, and prone to misidentifications especially when considering Amazonian species. The aim of this study was therefore to develop a DNA-based identification technique to supplement traditional morphological identification methods for the discrimination of anopheline mosquitoes collected in French Guiana. The internal transcribed spacer 2 (ITS2) region of ribosomal DNA (rDNA) for anopheline species was amplified by polymerase chain reaction (PCR), and digested with Alu I/ Msp I restriction enzymes. PCR-restriction fragments length polymorphism (RFLP) assay was compared to sequencing of the ITS2 region for validation. Fifteen Anopheles species have shown distinct PCR-RFLP profiles. A concordance of 100% was obtained when identification by PCR-RFLP was compared to sequencing of ITS2. A high throughput, fast, and cost-effective PCR-RFLP assay has been developed for unambiguous discrimination of fifteen anopheline mosquito species from French Guiana including primary and suspected secondary malaria vectors.